2002
DOI: 10.2166/nh.2002.0005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sub-Debris Thawing on Ablation and Runoff of the Djankuat Glacier in the Caucasus

Abstract: Superficial moraines grew in size during the entire 32-year-long period of direct monitoring of water and ice balance of the Djankuat Glacier in the Caucasus. The total area of debris cover on the glacier increased from 0.104 km2 (3% of the entire glacier surface) in 1968 to 0.266 km2 (8% of the glacier) in 1996. Such rapid dynamics of moraine formation greatly influences the ablation rate and distorts fields of mass-balance components. Sub-debris thawing can be calculated by means of a model, which describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 4 publications
10
36
0
Order By: Relevance
“…Rana et al (1996) reported an average thickness of debris cover of 0.5-1.0 m for the ablation area of Lirung glacier and Langtang glacier (Fig. 1) and therefore a reduction of melt is assumed (see Popovnin and Rozova, 2002). The additional parameter R debris (<1, -0) in Eq.…”
Section: Snow and Glacier Routinementioning
confidence: 99%
“…Rana et al (1996) reported an average thickness of debris cover of 0.5-1.0 m for the ablation area of Lirung glacier and Langtang glacier (Fig. 1) and therefore a reduction of melt is assumed (see Popovnin and Rozova, 2002). The additional parameter R debris (<1, -0) in Eq.…”
Section: Snow and Glacier Routinementioning
confidence: 99%
“…Information about the extent of debris cover is available for six years from in situ mapping between 1968 and 1999 (Popovnin and Rozova, 2002). In order to update this information, a Spot Image from 30 August 2006 (with a spatial resolution of 10 m) was used as a reference image for all remote sensing investigations including the glacier boundary delineation.…”
Section: Glacier and Debris Cover Mappingmentioning
confidence: 99%
“…According to our observations in the field, the transition between clean ice and a clearly identifiable debris cover is usually not very large on the sampled glaciers and wrong classifications will be of an order of a few pixels. The results were also compared with debris cover maps which exist for Djankuat glacier (Popovnin and Rozova, 2002) and newer mapping results. used a similar approach and achieved satisfactory results for the Djankuat glacier.…”
Section: Glacier and Debris Cover Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Greater Caucasus SDC is an important control for ice ablation, as it is similarly in many other glaciated areas (Lambrecht et al, 2011) 35 and has been identified as a key player in glacier mass balance (Popovnin and Rozova, 2002). In addition, in some cases SDC and proglacial lakes are directly related to glacial hazards.…”
Section: Introductionmentioning
confidence: 98%